Religious Values and Aspects of Teacher Empowerment Management - Imron Muttaqin; Abdul Razak Abdulroya Panaemalae (Al-Albab, 2019)
This article describes the religious values and aspects of teacher empowerment based on self-actualization theory. Literature studies was conducted, relevant research published on the online journal identified using Mendeley and Google Scholar Database. The study selection, data extraction and synthesis were carried independently. Thematic analysis was used to summarize religious values and aspects. The findings reveal religious values on the teacher empowerment based on self-actualization theory are religious, social, professional, humanist, kinship, and cooperation values. And there are six religious aspects in this theory; Ideological/aqeedah aspect, syari’ah, experiential, intellectual, professional, responsibility and harmony aspects. The implications of this study suggest effectively and harmony of all religious values and aspects for empowering teacher